Development of Sweet Corn Inbred Lines by Family Selection under Different Competition Environments - Nguyen Tien Truong; Krisda Samphantharak (Agriculture and Natural Resources, 2006)
Sweet corn (Zea mays L.) breeding has focused on quality and agronomic traits with yield performance as second priority trait. The objective of the present study was to compare yield and to combine ability of sweet corn inbred lines selected from 3 original single crossed under different competition environments; firstly, under high plant density (0.75 × 0.25 m); secondly, under low – competition spacing (0.866 m) in non – replicated honeycomb design; and thirdly, by alternate selection between the first 2 methods. The resulted 9 S3 family lines from each original hybrids were grouped into three line groups, totaling of 9 groups. Diallel cross was performed within each group, resulting in 27 intra – family hybrids. Simultaneously, they were crossed to a single cross, Insee2 to form 27 testcross hybrids. The results of the study showed that sweet corn inbred lines derived from selection under low – competition environment by honeycomb selection had not only higher yield but also higher combining ability compared with inbred lines derived from selection under high plant density environment and alternate selection between the first two methods. However, different sources of germplasm responded differently to the common tester.